Psychological Testing Theory - Buško, Vesna (2011)
Testing and assessment of individual differences has been a critical part of professional work of scientists and practitioners in psychology and related disciplines. It is generally acknowledged that psychological tests, along with the existing conceptualizations of measurements of human potentials, are among the most valuable contributions of behavioral sciences to the society. Testing practice is for many reasons an extremely sensitive not only professional but also a public issue. Because the decisions based on test results and their interpretations often entail important individual and societal consequences, psychological testing has been the target of profound public attention and a long-standing criticism (AERA, APA, & NCME, 1999).
Projekt MZOS
ENG